HUBUNGAN ANTARA EXPERIENCE ECONOMY, TOUR QUALITY, DAN TOUR SATISFACTION DI DESA WISATA TAMANMARTANI - Gilang Ahmad Fauzi; Fachrurrozi Rosyadi; Tegar Satya Putra; Desideria Cempaka Wijaya Murti; Prihatno (MANAJEMEN DEWANTARA, 2024)
This study aims to analyze the relationship between the dimensions of experience economy, tour quality, and tour satisfaction in Tamanmartani tourist village. The dimensions of experience economy consist of education, entertainment, aesthetic, escapism. Each of the dimension reflects specific expectation that the tour participants have to the tour itself. Through quantitative methods, questionnaires were used to collect data from tourists visiting Tamanmartani tourism village. A total of 100 respondents were involved in this study and the collected data were processed using Smart PLS. The result of the analysis shows that the dimensions of experience economy have a positive impact on the perception of tour quality and tour satisfaction. The results provide a better understanding of how the interaction between these factors can shape the perception, behavior, and image of tourist destinations. This study provides valuable information for destination managers, local governments, and tourism industry stakeholders to design more effective strategies in developing Tamanmartani tourism village.